COMPETITIVE STRATEGY THROUGH SUPPLY CHAIN MANAGEMENT ON PHARMACY INSTALLATION: COMPARISON STUDY IN TWO HOSPITALS - Cinthya Ratna Yuniar; Widi Hidayat (Airlangga Journal of Innovation Management, 2022)
Service-based business competition in hospitals can be achieved through cost leadership strategies without putting aside patient safety, differentiation strategies aims to differentiate themselves uniquely from competitors and focus strategies by targeting specific markets. The strategy series are 50% more influenced by the performance of Supply Chain Management at Pharmacy Installation. The purpose of this study is to evaluate the implementation of strategy and performance with the research subjects of the Hospital Type D Pharmacy Installation. The method of weighting the Analytical Hierarchy Process (AHP) was used to analyse the priority of strategy and performance assessment processed using the Objective Matrix (OMAX) method. The Supply Chain Operation Reference (SCOR) model is applied as a Key Performance indicator (KPI) with financial ratio data as a support for internal performance. The position of subject in competition and performance improvement benchmarks is seen through benchmarking with competitor of type C Hospital. Results of analysis show that the priority cost leadership strategy is supported by the AHP weighting cost of good sold 34.4% but the best performance is obtained from the order fulfillment cycle time 26.51%. Performance evaluation should be used by targets approaching competitor levels. The conclusion of this study, Hospital competing strategies can be obtained through synchronization of Supply Chain Management strategies and actual performance of Pharmacy Installation